Automotive service - Gilles, Tim (Delmar Publishers, 1999)
Automotive Service: Inspection, Maintenance & Repair covers the fundamentals of operation and repair for all major systems of the modern automobile. This comprehensive text introduces the fundamentals of systems and progresses onto diagnosis and service with thousands of lavish, full-color illustrations, Shop Tips, Safety Notes, and review questions to aid in comprehension. Traditional and new topics have been integrated in a concise, easy-to-read format: OBD II, ABS, engine performance, safety, and shop tools. Structured around the eight ASE automotive test areas, this book helps users prepare for ASE certification